A systematic review of lower limb strength tests used in elite basketball - Faulks, T.; Sansone, P.; Walter, S. (Sports, 2024)
Background: Basketball players rely on their lower limb strength for speed and agility. Therefore, it is important for strength and conditioning coaches to seek methods to assess and develop lower limb strength.